Evaluating the long-term impact of a distance learning course on attitudes, skills, practices, and knowledge in gender-affirming healthcare among healthcare professionals in Italy - Marconi, Matteo; Favazzi, Ughetta Maria; Carbone, Pietro; Guerrera, Debora; Ruocco, Angela; Manoli, Martina; Barbati, Cristiana; Molinaro, Francesca; Regini, Federica Maria; Vittozzi, Andrea; Mazzaccara, Alfonso; Pierdominici, Marina (Frontiers in Public Health, 2025)
IntroductionTransgender and gender-diverse (TGD) individuals face significant health disparities, often due to healthcare providers’ (HCPs) insufficient training and awareness. Comprehensive educational interventions are essential to improve both cultural competence and medical knowledge. While previous evaluations of training programs have shown short-term benefits, evidence on long-term outcomes remains scarce. This study extends the findings of an earlier evaluation of a distance learning course on TGD healthcare, exploring the sustainability of its effects over time.ObjectivesTo assess changes in self-reported attitudes, skills, practices, and knowledge retention 6 months after course completion.MethodsA longitudinal design was used with assessments at baseline (T0), post-course (T1), and six-month follow-up (T2). Participants completed the Attitudes, Skills, and Practices Questionnaire (ASPQ) and a 10-item knowledge test at all time points. Paired t-tests were used to compare mean scores for attitudes and skills. Knowledge retention was analyzed with McNemar tests. Changes in practice items were evaluated using Cochran’s Q and Friedman tests for paired categorical data.ResultsA total of 3,102 participants (17% of the original cohort) completed the follow-up. All self-reported skills and most attitudes improved significantly from baseline to follow-up (p < 0.001 for skills; p ≤ 0.02 for attitudes), with modest declines from T1. Practice items showed significant variation over time (Cochran’s Q and Friedman tests, p < 0.001), though without a consistent increase in engagement. Knowledge improved in 8 of 10 items from baseline to follow-up (McNemar, p < 0.001), particularly in sexual identity, hormone therapy, and legal rights, despite partial declines from post-course levels.ConclusionThis study highlights sustained improvements in self-reported attitudes, skills, and knowledge following a national TGD healthcare training, reinforcing its value in addressing health disparities. The findings underscore the need for structural support and integrated reinforcement to embed gender-affirming care into routine practice.